+0  
 
0
3
3420
2
avatar

For what value of b will the polynomial P(x) = 4x^3 - 3x^2 + bx + 6 have the same remainder when it is divided by both x - 1 and x + 3?

Guest May 11, 2015

Best Answer 

 #1
avatar+87301 
+10

4x^3 - 3x^2 + bx + 6  ... we can use the Remainder Theorem, here

So, if he remainders are equal, we have

4(1)^3 - 3(1)^2 + b(1) + 6 = 4(-3)^3 - 3(-3)^2 + b(-3) + 6

4 - 3 + b = -108 - 27 - 3b   simplify

1 + b = -135 - 3b

136 = -4b

b = -34

 

 

  

CPhill  May 11, 2015
 #1
avatar+87301 
+10
Best Answer

4x^3 - 3x^2 + bx + 6  ... we can use the Remainder Theorem, here

So, if he remainders are equal, we have

4(1)^3 - 3(1)^2 + b(1) + 6 = 4(-3)^3 - 3(-3)^2 + b(-3) + 6

4 - 3 + b = -108 - 27 - 3b   simplify

1 + b = -135 - 3b

136 = -4b

b = -34

 

 

  

CPhill  May 11, 2015
 #2
avatar
+5

thank you so much 

Guest May 11, 2015

16 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.